Foraging behaviour of four albatross species by night and day - Phalan, Ben (2012)
We integrated information from satellite transmitters, GPS loggers and wet/dry activity loggers to compare the at-sea behaviour of 4 sympatric albatross species by night and day: wandering Diomedea exulans, grey-headed Thalassarche chrysostoma, black-browed T. melanophrys and light-mantled sooty Phoebetria palpebrata (in total, 350 foraging trips by 101 individuals). Trip duration, distance and maximum range varied more within species between stages (incubation, broodguard and post-brood) than between species at the same stage, implying that reproductive constraints are more important than interspecific competition in shaping foraging behaviour. Wandering albatrosses spent more time on the water in fewer, longer bouts than other species. The proportion of time spent on the water was similar among the 3 smaller species. The partitioning of foraging activity between day and night varied little between species: all landed and took off more often, but spent less time overall on the water during the day than at night. This supports observations that albatrosses forage most actively during daylight, even though many of their fish and squid prey approach the surface only at night. Albatrosses were more active on bright moonlit nights, seem to have no fixed daily requirement for sleep, rest or digestion time on the water, can navigate in darkness, and are probably unhindered by the slight reduction in mean wind strength at night. They are probably less active at night because their ability to see and capture prey from the air is reduced and it is then more energy-efficient for them to rest or to catch prey using a ‘sit-and-wait’ foraging strategy.